A Preliminary Study of DSM–5 PTSD Symptom Patterns in Veterans by Trauma Type. Issue 2 (21st January 2016) - Graham, Jessica; Legarreta, Margaret; North, Lindsey; DiMuzio, Jennifer; McGlade, Erin; Yurgelun-Todd, Deborah
Abstract : Posttraumatic stress disorder (PTSD) has a primary etiology in experiencing psychological trauma and the subsequent psychological sequelae ( American Psychiatric Association, 2013 ). There are multiple trauma types that may serve as the index trauma in PTSD. This exploratory study compared DSM–5 PTSD symptoms for 3 types of trauma in veterans: combat trauma ( n = 36), sexual trauma ( n = 21), and civilian trauma ( n = 21). Results indicated that veterans with combat trauma were likely to experience diminished interest and detachment and estrangement from others. Veterans with sexual trauma were likely to experience detachment and estrangement from others, sleep disturbances, and problems with concentration. Veterans with civilian traumas were less likely to meet criteria for PTSD and were less likely to experience a number of PTSD symptoms. Results of this preliminary study suggest that PTSD is not a unitary disorder, but a disorder characterized by different subtypes based on the precipitating trauma.